Lifestyle habits associated with screen time among pupils in Japan. Issue 2 (6th February 2021) - Kohyama, Jun
Abstract: Background: Media use is pervasive among pupils. This study aimed to determine lifestyle factors associated with screen time. Methods: The study used a cross‐sectional design, and 2, 722 questionnaires obtained from pupils in grades 5–12 were analyzed. Multiple regression analysis was used to determine significant lifestyle factors associated with screen time. Grade, gender, bedtime and waking time on both school days and non‐school days, academic performance, sleepiness, breakfast, dinner regularity, defecation habits, hours of after‐school activities, physical activity, and body mass index were used as the variables. Results: Significant regression formulae were obtained for all school types: adjusted R 2 / P values were 0.21/<0.001 for elementary school, 0.21/<0.001 for junior high school, and 0.14/<0.001 for high school. Later non‐school‐day bedtime (standardized regression coefficient/ P values were 0.14/< 0.001 for elementary school, 0.14/<0.001 for junior high school, and 0.09/<0.05 for high school) was significantly associated with increased screen time for all school types. In both elementary and junior high schools, more sleepiness (0.12/<0.001 for elementary school, 0.13/<0.001 for junior high school), shorter after‐school activity (−0.24/<0.001 for elementary school, −0.19/<0.001 for junior high school), and higher standardized body mass index (0.08/<0.05 for elementary school, 0.08/<0.01 for junior high school) were significantly associated with screen time increase. In both junior and senior high schools, breakfast skipping (0.15/<0.001 for junior school, 0.14/<0.001 for high school) revealed a significant association with screen time increase. Conclusions: Media use is associated with variable lifestyle habits. Effective approaches to reduce heavy media use remain to be determined.